An analysis of library fines and borrowing periods in selected academic libraries in Metro Manila - Tolentino, Sheryl U. (Institute of Library Science, University of the Philippines Diliman, 2002)
The imposition of fines for overdue books has been a long standing practice in academic libraries. Fines are assessed in order to make the rule on borrowing period effective. The study focused on the structure of fines and borrowing periods in different academic libraries in Metro Manila. This study was done during the 1st semester of academic year 2001-2002. Out of 38 academic library respondents, 20 questionnaires were usable. The objectives of the study were (1) to describe the distribution of fines, borrowing period and other related variables for circulation and reserve; 2) to determine the relationship between library fine and borrowing period for circulation and reserve; 3) to determine the relationship between circulation fine and reserve fine; 4) to determine the relationship between circulation borrowing period and reserve borrowing period; 5) to determine the relationship between circulation fine and circulation percentage of overdue books; and 6) to determine the relationship between circulation borrowing period and circulation percentage of overdue books.